HUBUNGAN KUALITAS PELAYANAN KARYAWAN FRONT OFFICE DEPARTMENT DENGAN KEPUASAN PELANGGAN DI HOTEL ROCKY PLAZA PADANG - Ananda, Prima Rizki; Chair, Ira Meirina; Abrian, Youmil (Journal of Home Economics and Tourism, 2015)
This study originated from the observation and experience of researcherâ€™s friend while conducting industrial practice in Hotel Rocky Plaza Padang, that customer dissatisfaction with service quality front office employees in servingÂ customers, such as slow response to the guests who will check-in and check-out, Customers have complained that the rooms booked was not in accordance with their wishes, as well as errors in the connecting line from the outside by phone parts provider and also the problem of lack of alacrity bellboy when guests need. Based on the above issues, this study aims to: 1) Describe the service quality front office employees Hotel Rocky Plaza Padang, 2) Describe guest satisfaction of Hotel Rocky Plaza Padang, and 3) To analyze the relationship between service quality front office employees with customer satisfaction in Hotel Rocky Plaza Padang.This type of research is classified to the correlational research. The population in this studied were all customers in stay or has been stayed in Hotel Rocky Plaza Padang. These samples included 98 customers who are staying at the Rocky Plaza Hotel in Padang during the study period with the sampling technique is incidental sampling. Data was collected using a questionnaire by using a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed through descriptive analysis and correlation with the help of computer program SPSS version 17.00.The research found that: 1) Quality of Service Front Office located at the bad category (35%), 2) Customer satisfaction is In Category enough (40%), 3) test results Corelasi Product Moment with a significance level of 0.05, there is a relationship which positive and significant relationship between Service Quality Customer Satisfaction Front office with the r value of 0.479 (sig 0,000).